2006
DOI: 10.1016/j.jallcom.2005.03.127
|View full text |Cite
|
Sign up to set email alerts
|

MgNi/Pd multilayer hydrogen storage thin films prepared by dc magnetron sputtering

Abstract: MgNi/Pd multilayer thin films were deposited on Ni substrate by direct current (dc) magnetron sputtering using a dual-target, each MgNi layer being 40 nm and each Pd layer being 16 nm in thickness. The total thickness of the MgNi/Pd multilayer thin film is about 1.7 m. X-ray diffraction and scanning electron microscopy analysis revealed that the microstructure of the MgNi layer is amorphous and/or nanocrystalline and that the microstructure of the Pd layer is fine grained crystalline with no preferential orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…It can be seen from the values of S and r that the fitting is in excellent agreement with the experiment data. This result confirms that the hydriding reaction of the Mg 3 Mm alloy obeys the nucleation and growth mechanism, which is similar to other metal hydride [7]. However, different m values indicate different rate controlling step of nucleation and growth reaction.…”
Section: Hydrogen Storage Properties Of Mg 3 MM and Mg 3 Mmni 01 Alloysupporting
confidence: 83%
See 1 more Smart Citation
“…It can be seen from the values of S and r that the fitting is in excellent agreement with the experiment data. This result confirms that the hydriding reaction of the Mg 3 Mm alloy obeys the nucleation and growth mechanism, which is similar to other metal hydride [7]. However, different m values indicate different rate controlling step of nucleation and growth reaction.…”
Section: Hydrogen Storage Properties Of Mg 3 MM and Mg 3 Mmni 01 Alloysupporting
confidence: 83%
“…However, the kinetic properties, hydrogen absorption/desorption temperature and pressure of dehydriding in those materials are not suitable for practical application yet. In order to improve the kinetic properties of Mg based alloys, different methods, such as alloying element substitution [1][2][3], catalysts addition [4,5], surface modification [6] and non-equilibrium microstructure formation [7][8][9] have been applied. Although many new results have been reported, the kinetics properties for those materials are still a key problem to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable enhancement of the hydrogen sorption kinetics in the Mg/Pd thin films has been reported in other works, which used different thin films preparation and hydrogen loading conditions [10,11]. Moreover, other additives have been added to Mg-based thin films for improving their hydrogen sorption kinetic and thermodynamic properties, such as Cu [12], Ti [9], Mg-Ti-Fe [13], and Ni [14,15].…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, the PES (Photoelectron Spectroscopy) demonstrated that no Mg segregation or desorption occurs when hydrogen is desorbed from the film, rendering the system reversible. The PCI measurement of amorphous MgNi/Pd multilayer thin films deposited on Ni substrate by magnetron sputtering revealed that up to 4.6 wt% of hydrogen can be loaded to the films at room temperature [75]. Approximately the same, reversible hydrogen content of 4.45 wt% at 224 °C has been obtained for the 1160 nm thick Mg2.9Ni film [76].…”
Section: Binary and Ternary Mg-based Alloysmentioning
confidence: 84%